A flow-free droplet-based device for high throughput polymorphic crystallization1. Issue 12 (21st June 2015) - Yang, Shih-Mo; Zhang, Dapeng; Chen, Wang; Chen, Shih-Chi
<x xml:space="preserve">Abstract</x> Arrays of NaCl crystal nucleation and crystal growth on a flow-free droplet-based device.